2004
DOI: 10.1097/01.ta.0000141028.97753.67
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Radiation Dose Caused By Radiologic Studies in Critically Ill Trauma Patients

Abstract: From a radiobiologic perspective, risk-to-benefit ratios of radiologic studies are favorable, given the importance of medical information obtained. Current practice patterns regarding use of radiologic studies appear to be acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…4 More specifically, while the majority (80% to 85%) of human radiation exposure arises from equal amounts of solar and radon sources (background dose 1-3 mSv/yr), medical imaging creates most of the remaining 15% to 20%. 3,27,29,30 Furthermore, abdominal CT imaging accounted for up to 31% of the annual cumulative effective dose from medical imaging procedures in a study of nearly 1 million nonelderly adults. 4 Although many clinicians would argue that the vast majority of inpatient imaging is necessary to the care of pancreatic patients, it is clearly important that as physicians we evaluate both the volume of our imaging, as well as its true utility (i.e., ability to alter care).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 More specifically, while the majority (80% to 85%) of human radiation exposure arises from equal amounts of solar and radon sources (background dose 1-3 mSv/yr), medical imaging creates most of the remaining 15% to 20%. 3,27,29,30 Furthermore, abdominal CT imaging accounted for up to 31% of the annual cumulative effective dose from medical imaging procedures in a study of nearly 1 million nonelderly adults. 4 Although many clinicians would argue that the vast majority of inpatient imaging is necessary to the care of pancreatic patients, it is clearly important that as physicians we evaluate both the volume of our imaging, as well as its true utility (i.e., ability to alter care).…”
Section: Discussionmentioning
confidence: 99%
“…While ultrasonography, MRCP and endoscopic ultra sonography have the benefit of avoiding the delivery of ionizing radiation to patients, CT and the fluoroscopy associated with ERCP and IOC carry potential stochastic risks. Given the explosion in CT scanner use and indications 1,7,[18][19][20][21][22][23][24][25][26][27][28] (3 million CTs performed in 1980 v. 62 million in 2006), 8 radiation exposure is always a public health concern. This is evident in the nearly 6-fold increase in the per capita radiation exposure delivered from medical imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A study in which only patients with a LOS >30 days were included unsurprisingly showed higher radiation doses (mean cumulative dose 106 mSv) than that seen in our population. 11 Another study that measured radiation dose using dosimeters directly attached to patients for the entirety of their LOS (median 15 days) showed a median dose of 22.7 mSv. 10 Despite initial trauma scanning contributing to the largest proportion of radiation exposure, the consensus amongst clinicians involved in the management of trauma is that the risks of exposure to ionising radiation at this stage are probably outweighed by the potential risk of missing occult injuries.…”
Section: Discussionmentioning
confidence: 99%
“…11 This has led to suggestions that selective CT scanning may be more appropriate and a large, multicentre randomised trial is in progress that compares whole-body CT scanning with conventional radiographic imaging in conjunction with selective CT scanning. 12 Most of the current data on radiation exposure in trauma patients come from North American and Canadian populations.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 CT use in the investigation of trauma patients has increased significantly during the past two decades, 3 which may further increase the burden of radiationinduced malignancy on society. Several recent studies [4][5][6][7][8][9] have examined the radiation dose to trauma patients during their hospital stay, but only one study 8 has examined the radiation exposure associated with the patient's resuscitative phase of care and diagnosis. This study by Winslow et al excluded the most severelyinjured patients and did not consider tests done at referring centres, despite evidence to show that patients who are transferred from regional centres have higher total doses of radiation than those imaged at the trauma centre only.…”
Section: Introductionmentioning
confidence: 99%